Validation of MIPAS and SCIAMACHY data by ground-based spectroscopy at Kiruna, Sweden, and Izana, Tenerife Island (AO-191) in ESA SP-531 - Blumenstock, Thomas; Griesfeller, Alexandra; Hase, Frank; Schneider, Matthias; Fischer, Herbert; Gil, Manfred; Moreta, J.R.; Raffalski, Uwe; Friess, U.; Schwarz, Gottfried; Cuevas, Emilio (2003)
Measurements taken by MIPAS and SCIAMACHY are compared with ground-based observations